2019
DOI: 10.1111/bcp.13871
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of exudative age‐related macular degeneration with aflibercept combined with pranoprofen eye drops or nutraceutical support with omega‐3: A randomized trial

Abstract: Aims: The aim of this study was to determine whether a combination of intravitreal aflibercept (IVA) and pranoprofen eyedrops or nutraceutical support provides additional benefit over IVA monotherapy for the treatment of choroidal neovascularization (CNV) in age-related macular degeneration.Methods: This was a prospective, randomized, pilot study in 60 patients with treatmentnaïve CNV. Patients were randomized 1:1:1 into three groups: aflibercept monotherapy (AM), aflibercept plus pranoprofen (AP) or afliberce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…After 12 months of treatment, results showed that compared with AM, each combination group showed an improvement, although no significant benefits in BCVA were found over AM. More specifically, nutraceutical support with omega-3 led to a decreased need for intravitreal injections [ 271 ]. Moreover, therapeutic intravitreal drug injections can be given only a few times per year, while nutraceuticals can be used on a daily basis, so that their presence in the organism and their function are continuous and may improve patients’ responses to therapy while also alleviating its side effects.…”
Section: Nutraceuticals: Which Place In the Management Of Neovascular...mentioning
confidence: 99%
“…After 12 months of treatment, results showed that compared with AM, each combination group showed an improvement, although no significant benefits in BCVA were found over AM. More specifically, nutraceutical support with omega-3 led to a decreased need for intravitreal injections [ 271 ]. Moreover, therapeutic intravitreal drug injections can be given only a few times per year, while nutraceuticals can be used on a daily basis, so that their presence in the organism and their function are continuous and may improve patients’ responses to therapy while also alleviating its side effects.…”
Section: Nutraceuticals: Which Place In the Management Of Neovascular...mentioning
confidence: 99%
“…It's reported that sodium hyaluronate eye drops may dilute the tear that naturally secreted by human body and stimulate the tear gland. The application of sodium hyaluronate eye drops can temporarily relieve symptoms of dry eye, but the efficacy was not significant (Rongfeng, 2019;Semeraro et al, 2019;Zhu et al, 2018). Pranoprofen eye drops play antibacteria and anti-allergy effect, with significant action of relieving discomfort symptoms in eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies of course suffer from the problem that many different molecules are given at the same time and again would benefit from a more pharmacological mechanistic approach. 18 Clinical pharmacologists have to play a more important role in the development of these treatments than they do at present. We therefore hope that the number of ophtalmo-pharmacological submissions to BJCP will reflect that vision.…”
mentioning
confidence: 99%
“…Nutrition is not a medicine but the trial methodology similar especially when it is attempted to accomplish improvement of a condition like macular degeneration. Such studies of course suffer from the problem that many different molecules are given at the same time and again would benefit from a more pharmacological mechanistic approach 18 …”
mentioning
confidence: 99%